P032 Hepatocyte growth factor and MET in ulcerative colitis, novel drug targets impairing neutrophil recruitment?. (25th January 2019) - Verstockt, B; Stakenborg, M; Wollants, W-J; Van Assche, G; Ferrante, M; Vermeire, S; Matteoli, G
Abstract: Background: Neutrophils are crucial in the maintenance of intestinal homeostasis and inflammation. However, during chronic inflammatory conditions, like inflammatory bowel disease (IBD), the intestinal immune system responds inaccurately resulting in excessive neutrophil infiltration and tissue damage. MET is a tyrosine kinase required for neutrophil chemoattraction and cytotoxicity in response to its ligand hepatocyte growth factor (HGF). A neutrophil specific deletion of MET improved the severity of chronic DSS-colitis, together with reduced immune cell infiltration. We aimed to study HGF levels in blood and tissue of patients with ulcerative colitis (UC) and healthy controls (HC). Methods: We collected serum in HC and actively inflamed UC patients, prior to the start of anti-TNF therapy, and at endoscopic reassessment (8–14 weeks after treatment initiation). Endoscopic remission was defined as a Mayo endoscopic sub-score ≤1. HGF was measured using the MesoScale Discovery electrochemiluminescence technology (MSD, Rockville, USA). Additionally, RNA sequencing (Illumina HiSeq4000) was performed on inflamed colonic biopsies in a subset of 24 UC patients and 11 HC. Results: Serum HGF was significantly up-regulated in 110 active UC patients compared with 30 HC ( p = 0.001, fold change FC 1.5). Similarly, colonic HGF and MET expression were significantly up-regulated compared with healthy individuals ( p = 3.2E10–6, FC 5.8; p = 0.0007, FC 1.8, respectively). Serum HGF correlated significantly with tissue MET expression ( r = 0.47, p = 0.03), but not with tissue HGF expression ( r = 0.23, p = 0.30). Patients with a Mayo endoscopic sub-score of 3 had significantly higher serum HGF levels when compared with patients with a sub-score of 2 prior to therapy initiation ( p = 0.007, FC 1.2). Additionally, serum HGF levels correlated significantly with C-reactive protein ( r = 0.44, p = 9.5E10–12), and absolute neutrophils counts ( r = 0.62, p = 2.2E10–16). However, baseline HGF was not predictive for anti-TNF-induced endoscopic remission later on ( p = 0.39). After anti-TNF administration, HGF levels overall decreased ( p = 1.2E10–7) and reached values of HC in case of endoscopic remission ( p = 0.35, n = 54), but not in case of non-remission ( p = 0.04, n = 56). At the time of endoscopic assessment, patients with endoscopic remission had significantly lower HGF levels than those without ( p = 0.0003, FC 0.72). Conclusions: Colonic and serum HGF levels are significantly up-regulated in active UC patients, with restoration towards physiological levels in patients with anti-TNF-induced endoscopic remission. As murine findings earlier suggested that absence of MET in neutrophils reduces intestinal inflammation, targeting MET could be considered as a novel therapeutic approach in UC therapy.